Arterial hypertension in patients under antineoplastic therapy: a systematic review. Issue 5 (May 2019) - Katsi, Vasiliki; Magkas, Nikolaos; Georgiopoulos, Georgios; Athanasiadi, Eleni; Virdis, Agostino; Masi, Stefano; Kliridis, Panagiotis; Hatziyanni, Amalia; Tsioufis, Costas; Tousoulis, Dimitrios
Abstract : Background: Cardio-oncology aims to mitigate adverse cardiovascular manifestations in cancer survivors, but treatment-induced hypertension or aggravated hypertension has received less attention in these high cardiovascular risk patients. Methods: In this systematic review, we searched literature for contemporary data on the prevalence, pathophysiologic mechanisms, treatment implications and preventive strategies of hypertension in patients under antineoplastic therapy. Results: Several classes of antineoplastic drugs, including mainly vascular endothelial growth factor inhibitors, proteasome inhibitors, cisplatin derivatives, corticosteroids or radiation therapy were consistently associated with increased odds for new-onset hypertension or labile hypertensive status in previous controlled patients. Moreover, hypertension constitutes a major risk factor for chemotherapy-induced cardiotoxicity, which is the most serious cardiovascular adverse effect of antineoplastic therapy. Despite the heterogeneity of pooled studies, the pro-hypertensive profile of examined drug classes could be attributed to common structural and functional disorders. Importantly, certain antihypertensive drugs are considered to be more effective in the management of hypertension in this population and may partially attenuate indirect complications of cancer treatment, such as progressive development of cardiomyopathy and/or cardiovascular death. Nonpharmacological approaches to alleviate hypertension in cancer patients are also described, albeit adjudicated as less effective in general. Conclusion: A growing body of evidence suggests that multiple antineoplastic agents increase the rate of progression of hypertension. Physicians need to balance the life-saving cancer treatment and the inflated risk of adverse cardiovascular events due to suboptimal management of hypertension in order to achieve improved clinical outcomes and sustained survival for their patients.